2014
DOI: 10.1007/s00167-014-2953-1
|View full text |Cite
|
Sign up to set email alerts
|

Midterm results following medial closed wedge distal femoral osteotomy stabilized with a locking internal fixation device

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 37 publications
5
60
0
1
Order By: Relevance
“…They compared the failed-group and the nonfailed one, and they stated that in the failed group, the average age was significantly higher [38]. On the other hand, Forkel et al analyzed different variables potentially correlated with the outcome of DFO; they found that neither age nor presence of associated microfractures affected the result [39]. Afterward, different authors described their results with slight modification of the original surgical technique.…”
Section: Medial Closing Wedgementioning
confidence: 99%
“…They compared the failed-group and the nonfailed one, and they stated that in the failed group, the average age was significantly higher [38]. On the other hand, Forkel et al analyzed different variables potentially correlated with the outcome of DFO; they found that neither age nor presence of associated microfractures affected the result [39]. Afterward, different authors described their results with slight modification of the original surgical technique.…”
Section: Medial Closing Wedgementioning
confidence: 99%
“…The authors concluded that overcorrecting the osteotomy of 5° normalize contact pressure and contact areas in the lateral compartment (23). Similarly, others authors reported good clinical outcomes with valgus deformity over-correction (mechanical axis goal at 40-41% of tibial plateau) due to lateral compartment unloading and medial muscles' forces neutralization (20,24).…”
Section: Preoperative Settingmentioning
confidence: 92%
“…Recently Forkel et al (24) described their surgical technique: bone cuts were performed at the same way described by Healy et al (27) but the osteotomies were fixed with locking plates. This fixation may increase the stability of the osteotomy and reduce the time of post-operative weight bearing limitation (13,24).…”
Section: Medial Closing-wedge Osteotomymentioning
confidence: 99%
“…Contraindications to the procedure include inflammatory arthritis, flexion contracture of greater than 15 , knee flexion of less than 90 , fixed valgus deformity of greater than 20 , and arthritis in the medial or patellofemoral compartments. 1,7,9 Patient Positioning and Anesthesia…”
Section: Varus-producing Dfo Indicationsmentioning
confidence: 99%
“…[2][3][4] Recently, the indications for varus-producing DFOs have expanded to include the treatment of valgus malalignment in the setting of central or medial ligamentous instability or incompetence. [5][6][7][8][9][10][11][12][13][14] This is of particular importance and utility because several authors have also reported that healing of both the native and reconstructed medial collateral ligament (MCL) is impaired with persistent valgus deformity at the knee. 6 For this reason, many surgeons now choose to perform a DFO to correct the valgus deformity at the knee not only in the setting of isolated lateral compartment pathology but also in the setting of medial ligamentous incompetence.…”
mentioning
confidence: 99%